Cu-Ti composite hybrid metal-organic framework, photoelectrode or device comprising the same for adsorption or decomposition of volatile organic compound, and preparation process thereof
Patent Information
- Application Number
- KR1020240075778
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-06-11
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2044-06-11
Smart Images

Figure 112024062897800-PAT00002_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a copper-titanium composite hybrid metal-organic framework, a photocatalyst or device for adsorbing or decomposing volatile organic compounds comprising the same, and a method for manufacturing the same. Background Technology
[0002] Aromatic compounds are one of the most common volatile organic compounds (VOCs), generated in large quantities from sources such as automobiles, industrial applications, and construction materials, and act as major toxic air pollutants. Among recent technologies, combining the adsorption of aromatic compounds with photocatalytic technology is recognized as an effective method for removing aromatic compounds under mild operating conditions.
[0003] Metal-Organic Frameworks (MOFs) consist of inorganic metal nodes and organic ligands and demonstrate high potential for utilization in various applications. In particular, they possess high potential for the adsorption of volatile organic compounds and photocatalysis due to their very large surface area, tunable pore size, and unique physicochemical properties. Generally, the organic linker (HOMO) of a metal-organic framework generates photogenerated electrons upon irradiation with light, and these electrons move to the metal cluster (LUMO) of the framework through a channel connected between the linker and the metal. However, a disadvantage is the low photoactivity caused by the slow charge separation of metal-organic frameworks.
[0004] Meanwhile, titanium dioxide or titania (TiO2), the most widely used photocatalyst for the decomposition of gaseous pollutants, possesses many advantages such as low cost, excellent stability, and non-toxicity. However, its use is limited due to its wide bandgap (3.2 eV), strong tendency for charge recombination, and low surface area.
[0005] Accordingly, attempts have been made to overcome the shortcomings of the aforementioned MOFs and titanium dioxide by combining MOFs such as MIL-101, PCN-22, and ZIF-8 with TiO2. These attempts demonstrated improved photocatalytic performance by promoting charge transfer and increased light absorption through an expanded surface area. However, most of these MOF / TiO2 heterocomposites are bonded via non-covalent bonds, which limits their ability to provide the stability associated with covalent bonding.
[0006] Therefore, interest in the performance of heterocomposites with covalent structures has recently been increasing; for example, studies have been reported on composites in which TiO2 is covalently bonded to graphene, a substrate functionalized with carboxyl groups, through carboxyl groups. In such composites, covalent bonding enhances the interaction between heterogeneous components and enables the control of electrical properties.
[0007] Meanwhile, although a one-pot solvothermal synthesis method for producing a photocatalyst comprising a copper-titanium composite hybrid metal-organic framework for the adsorption and decomposition of volatile organic compounds has been reported (Korean Patent Publication No. 10-2024-0011912), it is necessary to change the solvent and undergo additional processes to achieve a scale-up suitable for industrialization. Specifically, the aforementioned prior art utilizes a method in which titanium oxide and an organic linker are first reacted by a hydrothermal method to form an organic linker-titanium oxide conjugate, and then this is mixed with a copper compound and an additional organic linker to produce the composite.
[0008] Specifically, the existing one-pot solvothermal synthesis method has a solid yield of only 2-3%, which is sufficient for laboratory or small-scale applications, but it is necessary to increase it to over 10% for industrialization.
[0009] Furthermore, the existing one-pot solvothermal synthesis method is difficult to apply to industrialization because it requires the use of high-temperature, high-pressure reactors. Moreover, the solvents used are organic solvents harmful to the human body, such as dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-diethylformamide (DEF), N,N-dimethylacetamide (DMA) chloride (MC), and dimethyl chloride (DMC), creating a need to switch to environmentally friendly solvents. Meanwhile, technology regarding an apparatus for simultaneously manufacturing multiple types of metal-organic frameworks in a continuous process is also known (Published Patent Application No. 10-2023-0062375). Although the above technology describes that a pH regulator can be added to the reaction section of the metal precursor and ligand, this is intended for the simultaneous synthesis of pure MOFs such as ZIF-8 and Fe-BTC, and is different in technical context from the synthesis of copper-titanium composite hybrid MOF / TiO2 composites.
[0010] Therefore, there is an urgent need to develop a method for manufacturing a copper-titanium composite hybrid metal-organic framework that maintains the adsorption and decomposition performance of volatile organic compounds of the titanium metal-organic framework photocatalyst, while enabling a solid content yield of at least 10% which is sufficient for industrialization, reactions at room temperature and atmospheric pressure, and the use of eco-friendly solvents.
[0011] In addition, there are problems such as the aggregation of titania during the composite manufacturing process, the reduction in strength and surface scratches during the pelletization process of the composite, the dependence of adsorption characteristics on manufacturing process conditions, and non-uniformity in pellet shape and size, so solving these remains a challenging task. Prior art literature
[65535] Published Patent Application No. 10-2024-0011912 Published Patent Application No. 10-2023-0062375 The problem to be solved
[0012] The present invention aims to provide a copper-titanium composite hybrid metal-organic framework capable of maintaining the adsorption and decomposition performance of volatile organic compounds of a titanium metal-organic framework photocatalyst, while enabling a solid content yield of at least 10% which is sufficient for industrialization, a reaction at room temperature and atmospheric pressure, and the use of an eco-friendly solvent, a photocatalyst or device for adsorbing or decomposing volatile organic compounds containing the same, and a method for manufacturing the same.
[0013] In addition, the present invention aims to provide a copper-titanium composite hybrid metal-organic framework capable of solving conventional technical problems such as aggregation of titania during the composite manufacturing process, reduction of strength and occurrence of surface scratches during the pelletization process of the composite, dependence of adsorption characteristics on manufacturing process conditions, and non-uniformity of pellet shape and size, a photocatalyst or device for adsorbing or decomposing volatile organic compounds containing the same, and a method for manufacturing the same. means of solving the problem
[0014] To this end, one aspect of the present invention provides a method for preparing a copper-titanium composite hybrid metal-organic framework comprising the steps of: (A) adding an organic ligand to a first solution containing a copper precursor and titania and stirring to obtain a second solution; (B) adding a pH adjuster solution to the second solution to obtain a third solution; and (C) separating a product from the third solution.
[0015] Another aspect of the present invention provides a copper-titanium composite hybrid metal-organic framework manufactured according to various embodiments of the present invention.
[0016] Another aspect of the present invention provides a photocatalyst for the adsorption or decomposition of volatile organic compounds comprising a copper-titanium composite hybrid metal-organic framework according to various embodiments of the present invention.
[0017] Another aspect of the present invention provides an apparatus for the adsorption or decomposition of volatile organic compounds comprising a photocatalyst for the adsorption or decomposition of volatile organic compounds according to various embodiments of the present invention. Effects of the invention
[0018] The copper-titanium composite hybrid metal-organic framework according to the present invention, the photocatalyst or device for adsorbing or decomposing volatile organic compounds including the same, and the method for manufacturing the same have the effect of maintaining the adsorption and decomposition performance of volatile organic compounds of the titanium metal-organic framework photocatalyst while enabling a solid content yield of at least 10%, which is sufficient for industrialization, reaction at room temperature and atmospheric pressure, and the use of an eco-friendly solvent.
[0019] In addition, the present invention can solve the conventional technical problems discussed above, such as the aggregation of titania during the composite manufacturing process, the reduction in strength and occurrence of surface scratches during the pelletization process of the composite, the dependence of adsorption characteristics on manufacturing process conditions, and the non-uniformity of pellet shape and size.
[0020] The effects of the present invention are not limited to those mentioned above and should be understood to include all effects that can be inferred from the following description. Brief explanation of the drawing
[0021] Figure 1 is the XRD analysis result of the composite prepared in Example 1. Specific details for implementing the invention
[0022] One aspect of the present invention relates to a method for preparing a copper-titanium composite hybrid metal-organic framework comprising the steps of: (A) adding an organic ligand to a first solution containing a copper precursor and titania and stirring to obtain a second solution; (B) adding a pH adjuster solution to the second solution to obtain a third solution; and (C) separating a product from the third solution.
[0023] As such, the present invention includes, as one of its constituent features, a first solution comprising a copper precursor and titania, and then an organic ligand is added to it and stirred to obtain a second solution. Additionally, the present invention includes, as one of its constituent features, a pH adjuster solution added to the second solution to obtain a third solution. Furthermore, the present invention includes a step of separating a product from the third solution thus obtained.
[0024] According to this configuration of the present invention, it can be manufactured at room temperature and atmospheric pressure using an eco-friendly solvent, and while maintaining the adsorption and decomposition performance of volatile organic compounds of existing titanium metal-organic framework photocatalysts, it has the advantage of showing a solid content yield of at least 10% by weight, which is sufficient for industrialization, as well as the advantage of resolving the aggregation of titania during the composite manufacturing process.
[0025] On the other hand, it was confirmed that unlike the present invention, if the copper precursor, titania, and organic ligand are added together to prepare the solution at once, or if a pH adjuster is not added, the solid yield may be significantly reduced, or depending on the manufacturing process conditions, aggregation of titania may occur, which may affect the adsorption performance of volatile organic compounds or photocatalytic performance.
[0026] In one embodiment, examples of copper precursors usable in the present invention may include one or more selected from copper nitrate, cuprous chloride, cupric chloride, cuprous iodide, copper pyrophosphate, copper sulfate, copper bromide, cuprous oxide, cupric oxide, copper carbonate, copper acetate, or their respective hydrates, but are not limited thereto. Representative examples of copper precursors usable in the present invention may include Cu(NO3)2·2.5H2O, but are not limited thereto.
[0027] In other embodiments, examples of pH adjusters usable in the present invention include one or more selected from sodium hydroxide, potassium hydroxide, ammonium hydroxide, hydrochloric acid, phosphoric acid, and nitric acid, but are not limited thereto.
[0028] According to another embodiment, the first solvent, which is the solvent of the first solution in the present invention, and the second solvent, which is the solvent of the second solution, may be the same or different from each other and may each be independently one or more selected from methanol, ethanol, isopropyl alcohol, acetone, benzene, hexane, diethyl ether, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), and N,N-diethylformamide (DEF), but are not limited thereto.
[0029] In another embodiment, in step (B) above, it is preferable that the pH adjuster be added at a rate of 1 mol : 50-100 mmol per minute based on the copper precursor. Additionally, in step (B) above, it is preferable that the pH adjuster be added at a constant rate.
[0030] In contrast, it was confirmed that if a pH adjuster is added at a rate outside the range of 1 mol : 50-100 mmol based on the copper precursor, or if it is added at an inconsistent rate even within the above range, problems may arise, particularly in pelletization, where pellets with insufficient strength and visible scratches on the surface may be produced depending on the process conditions.
[0031] In another embodiment, in step (A) above, it is preferable that the copper precursor, titania, and organic ligand be introduced in a molar ratio of 1:1-1.5:0.3-0.7.
[0032] In contrast, it was confirmed that when the input molar ratio of copper precursor, titania, and organic ligand falls outside the above range, problems may arise in which the adsorption characteristics of the copper-titania composite hybrid metal-organic framework prepared in this way exhibit a significant dependence on reaction conditions, such as variations in the adsorption rate or adsorption rate of volatile organic compounds depending on the type of pH regulator or the type of copper precursor.
[0033] In another embodiment, in step (B), it is preferable that the pH adjuster be added in a molar ratio of 1:1.2-1.7 based on the copper precursor.
[0034] In contrast, it was confirmed that when the amount of pH adjuster based on the copper precursor is within the above molar ratio range, the shape and size of the pellets are manufactured uniformly, whereas when it falls outside the above range, problems may arise where the shape or size of the manufactured pellets becomes non-uniform depending on the manufacturing process conditions.
[0035] Another aspect of the present invention relates to a copper-titanium composite hybrid metal-organic framework manufactured according to various embodiments of the present invention.
[0036] Another aspect of the present invention relates to a photocatalyst for the adsorption or decomposition of volatile organic compounds comprising a copper-titanium composite hybrid metal-organic framework according to various embodiments of the present invention.
[0037] Another aspect of the present invention relates to an apparatus for the adsorption or decomposition of volatile organic compounds comprising a photocatalyst for the adsorption or decomposition of volatile organic compounds according to various embodiments of the present invention.
[0038] Detailed embodiments of the present invention are described below. The following embodiments illustrate specific examples of how the present invention is practiced, but they are intended to clarify the understanding of the invention and the invention is not limited to the content of these embodiments.
[0039] Examples
[0040] Example 1
[0041] (1) Synthesis of copper-titanium composite hybrid metal-organic framework (CW-01 composite)
[0042] 4.80 kg of copper precursor (Cu(NO3)2·2.5H2O, molecular weight 232.59), titania (titanium dioxide, molecular weight 79.87, aeroxide) ® 2.0 kg of ) was added to 63.35 kg of methanol and stirred for 2 hours. The weight ratio of copper precursor to titania is 1:0.417, and the molar ratio is 1:1.213.
[0043] Next, 2.09 kg of organic ligand (trimesic acid, benzene-1,3,5-tricarboxylic acid, H3BTC, molecular weight 210.14) was added to the mixture and stirred for an additional 2 hours to obtain a mixed solution containing a copper precursor, titania, and an organic ligand. The weight ratio of the copper precursor to the organic ligand is 1:0.435, and the molar ratio is 1:0.482.
[0044] Next, 1.20 kg of sodium hydroxide (NaOH, molecular weight 40), a pH adjuster, was added to the above mixed solution in a solution prepared by dissolving it in 4.75 kg of methanol, at a rate of 0.06 kg / min. The weight ratio of the copper precursor to the pH adjuster was 1:0.25 and the molar ratio was 1:1.454, and the weight ratio of the amount of copper precursor added to the amount of pH adjuster added per minute was 1:0.0125 and the molar ratio was 1:0.0727.
[0045] The blue product obtained in this way was separated, then washed sequentially twice with methanol and three times with ethanol, and dried in an oven at 70°C to obtain a copper-titanium composite hybrid metal-organic framework (CW-01 composite) which is a copper-titanium composite combined with H3BTC.
[0046] (2) Pelleting of the CW-01 composite
[0047] The CW-01 composite synthesized above was kneaded and pellets were prepared using a pelletizing machine.
[0048] (3) As a result of synthesizing the above CW-01 composite, 16% by weight of solids was obtained even though the synthesis was performed at room temperature and commercially using methanol, which is much less harmful than the solvent used in the conventional one-pot solvothermal synthesis method, and no aggregation of titania was observed during the above manufacturing process.
[0049] In addition, as a result of pelletizing the above CW-01 composite, uniform pellets were produced that were dark purple in color, had an average diameter of about 3.5-4.5 mm, and were spherical in shape. They exhibited sufficient strength to be used as a photocatalyst, and no scratches were observed on the surface.
[0050] In addition, after producing pellets by changing the reaction conditions, such as the above stirring time (3 hours), additional stirring time (3 hours), and drying temperature (80℃), to the conditions in parentheses, the adsorption characteristics were compared with the pellets produced above as described in the test example below, and as a result, there was almost no difference from what is presented in the test example below, confirming that there is almost no dependence of the adsorption characteristics on the reaction conditions.
[0051] Comparative Examples 1 to 3
[0052] (1) Prepared without adding pH adjuster (Comparative Example 1)
[0053] A copper-titanium composite hybrid metal-organic framework and pellets thereof, which are H3BTC-linked copper-titanium composites, were prepared in the same manner as in Example 1, except that the step of adding a methanol solution of a pH adjuster was omitted.
[0054] (2) One-pot preparation (pH regulator added, Comparative Example 2)
[0055] 4.80 kg of copper precursor (Cu(NO3)2·2.5H2O), titania (titanium dioxide, aeroxide) ® 2.0 kg of ) and 2.09 kg of organic ligand (trimesic acid, benzene-1,3,5-tricarboxylic acid, H3BTC) were added to 63.35 kg of methanol at once and stirred for 4 hours to obtain a mixed solution containing copper precursor, titania and organic ligand.
[0056] Next, a solution of 1.20 kg of sodium hydroxide (NaOH), a pH adjuster, dissolved in 4.75 kg of methanol was added to the above mixture, with the sodium hydroxide being added at a rate of 0.06 kg / min.
[0057] The remainder involved preparing a copper-titanium composite hybrid metal-organic framework and pellets thereof, which are copper-titanium composites combined with H3BTC, in the same manner as in Example 1.
[0058] (3) One-pot preparation (without pH adjuster, Comparative Example 3)
[0059] 4.80 kg of copper precursor (Cu(NO3)2·2.5H2O), titania (titanium dioxide, aeroxide) ® 2.0 kg of ) and 2.09 kg of organic ligand (trimesic acid, benzene-1,3,5-tricarboxylic acid, H3BTC) were added to 63.35 kg of methanol at once and stirred for 4 hours to obtain a copper-titanium composite hybrid metal-organic framework, which is a copper-titanium composite combined with H3BTC, and pellets were prepared using the same method as in Example 1.
[0060] (4) In Comparative Examples 1 to 3 above, the solid content yield was 6.5 wt%, 7.1 wt%, and 5.9 wt%, respectively, which was significantly lower than that of Example 1.
[0061] In addition, aggregation of titania during the manufacturing process, which affects the adsorption performance of volatile organic compounds or photocatalytic performance, was also observed visually.
[0062] Comparative Example 4: Temporary addition of pH adjuster
[0063] Copper-titanium composite hybrid metal-organic frameworks and pellets thereof, which are copper-titanium composites combined with H3BTC, were prepared in the same manner as in Example 1, except that the entire methanol solution of sodium hydroxide was introduced at once instead of sodium hydroxide being introduced at a rate of 0.06 kg / min.
[0064] It was confirmed that the strength of the manufactured pellets was reduced, with the strength being only 63.1% of that of Example 1, and scratches on the surface of a significant number of pellets were also observed visually.
[0065] Comparative Example 5
[0066] Copper-titanium composite hybrid metal-organic frameworks and pellets thereof, which are copper-titanium composites combined with H3BTC, were prepared in the same manner as in Example 1, except that the input molar ratio of copper precursor to titania was changed to 1:1.55 instead of 1:1.213.
[0067] The adsorption characteristics of the pellets prepared in this way were measured as described in the test examples below. Meanwhile, after preparing pellets by changing the reaction conditions, such as stirring time (3 hours), additional stirring time (3 hours), and drying temperature (80°C), to the conditions in parentheses, the adsorption characteristics were compared with those of the pellets prepared above. As a result, the former showed a reduced adsorption rate and adsorption rate of 87% and 79%, respectively, compared to the latter, confirming the dependence of adsorption characteristics on reaction conditions.
[0068] Comparative Example 6
[0069] Copper-titanium composite hybrid metal-organic frameworks and pellets thereof, which are copper-titanium composites combined with H3BTC, were prepared in the same manner as in Example 1, except that the molar ratio of the copper precursor to the organic ligand input was changed to 1:0.73 instead of 1:0.482.
[0070] It was confirmed that the obtained pellets were non-uniform in size, with an average diameter ranging from as small as 1 mm to as large as 7 mm, and that many pellets were produced in the shape of distorted spherical or ellipsoidal forms.
[0071] Test Example 1: XRD and BET analysis of CW-01 complex
[0072] X-ray diffraction (XRD) analysis was performed on the CW-01 composite prepared in Example 1 above. As a result, it was confirmed that the X-ray diffraction pattern of the pure copper-organic framework and the X-ray diffraction pattern of the titania were combined.
[0073] Test Example 1-2: Evaluation of VOC Adsorption and Photocatalytic Activity of CW-01 Composite
[0074] To evaluate the VOC adsorption capacity and photocatalytic activity of the CW-01 composite prepared in Example 1 above, a toluene removal test of 110 ppm was conducted in a self-designed closed-circulation type reactor, and the degree of toluene decomposition was calculated based on the concentration of CO2 emitted from the reactor.
[0075] Specifically, 110 ppm of toluene was injected and allowed to evaporate within the reactor, and when equilibrium between adsorption and desorption was reached, a sample was irradiated using a solar simulator (Peccell, Yokohama, Japan, PEC-L01). The removal efficiency was calculated according to the following equation (unit: ppm).
[0076]
[0077] In the above formula, C i,toluene is the theoretical toluene injection concentration, and C 0,co2 is the initial CO2 concentration in the reactor, and C t,co2 is the real-time CO2 concentration during photocatalytic action.
[0078] Test Example 1-3: Confirmation of the stability of the CW-01 complex
[0079] To confirm the stability of the CW-01 composite prepared in Example 1 above, a toluene removal experiment was repeated. It was confirmed that the mineralization efficiency of toluene did not decrease at all even after the third cycle.
Claims
Claim 1 A method for preparing a copper-titanium composite hybrid metal-organic framework comprising: (A) a step of adding an organic ligand to a first solution containing a copper precursor and titania and stirring to obtain a second solution; (B) a step of adding a pH adjuster solution to the second solution to obtain a third solution; and (C) a step of separating a product from the third solution. Claim 2 A method for manufacturing a copper-titanium composite hybrid metal-organic framework according to claim 1, wherein the copper precursor is one or more selected from copper nitrate, cuprous chloride, cuprous chloride, cuprous iodide, copper pyrophosphate, copper sulfate, copper bromide, cuprous oxide, cuprous oxide, copper carbonate, copper acetate, or each of these hydrates. Claim 3 A method for manufacturing a copper-titanium composite hybrid metal-organic framework, characterized in that, in claim 1, the pH adjuster is one or more selected from sodium hydroxide, potassium hydroxide, ammonium hydroxide, hydrochloric acid, phosphoric acid, and nitric acid. Claim 4 A method for manufacturing a copper-titanium composite hybrid metal-organic framework according to claim 1, wherein the first solvent, which is the solvent of the first solution, and the second solvent, which is the solvent of the second solution, are identical or different from each other and are each independently one or more selected from methanol, ethanol, isopropyl alcohol, acetone, benzene, hexane, diethyl ether, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), and N,N-diethylformamide (DEF). Claim 5 A method for manufacturing a copper-titanium composite hybrid metal-organic framework, characterized in that, in step (B) above, the pH adjuster is introduced at a rate of 1 mol : 50-100 mmol per minute based on the copper precursor. Claim 6 A method for manufacturing a copper-titanium composite hybrid metal-organic framework, characterized in that, in step (B) of claim 5, the pH adjuster is introduced at a constant rate. Claim 7 A method for manufacturing a copper-titanium composite hybrid metal-organic framework according to claim 1, characterized in that, in step (A), the copper precursor, the titania, and the organic ligand are introduced in a molar ratio of 1:1-1.5:0.3-0.
7. Claim 8 A method for manufacturing a copper-titanium composite hybrid metal-organic framework, characterized in that, in step (B) above, the pH adjuster is added in a molar ratio of 1:1.2-1.7 based on the copper precursor. Claim 9 A copper-titanium composite hybrid metal-organic framework manufactured according to any one of claims 1 to 8. Claim 10 A photocatalyst for the adsorption or decomposition of volatile organic compounds comprising a copper-titanium composite hybrid metal-organic framework according to claim 9. Claim 11 An adsorption or decomposition device for volatile organic compounds comprising a photocatalyst for adsorption or decomposition of volatile organic compounds according to paragraph 10.
Citation Information
Patent Citations
Composite material and manufacturing tmethod for the same
KR1020180027080A
Titanium-organic framework photocatalyst for adsorption and decomposition of volatile organic compound, manufacturing method thereof and method for removing volatile organic compound using titanium-organic framework photocatalyst
KR1020220148343A
p-xylene Selective Adsorbents and method for selectively separating p-xylene using the same
KR1020230158770A
Titanium heterometallic metal-organic solids, method for obtaining them and their uses
WO2019224413A1
Simultaneous manufacturing apparatus and method for simultaneous manufacturing of multiple types of metal-organic frameworks (MOF)
KR1020230062375A
